The phenomenon of ultractivity: the normative business clauses and the summary no. 277 of the TST - Junior, Romeu Felix Menin (Revista Coleta Científica, 2018)
The theme of this article is the phenomenon of ultra activity: The normative business clauses and the summary 277 of the Superior Labor Court - TST. The following problem was investigated: Is the Constitutional amendment to TST 277? The following hypothesis was considered: The allegations coming from the professional categories conflict with those from the economic category, would the summary measure be the middle ground for both categories? The general objective is to highlight a middle ground that pleases both parties in the employment contract within what is presented in the summary, the unconstitutionality of both parts of the summary is stipulated. The specific objectives are: the possible reflexes of the new understanding on future collective bargaining; criticism of the professional category; the criticism of the economic category. This work is important from a legal and social perspective as it aims to analyze the possible impacts on collective bargaining due to the change in the understanding of the TST. This article concluded that Súmula 277 is in conformity with the legal and constitutional precepts, both in relation to the formal aspect and in relation to the material aspects, according to the best doctrine This is a qualitative theoretical research lasting six months.